Nuclear receptors in ovarian cancer: changing paradigms in cancer therapeutics - Sajeev, Anjana; BharathwajChetty, Bandari; Manickasamy, Mukesh Kumar; Alqahtani, Mohammed S.; Abbas, Mohamed; Shakibaei, Mehdi; Sethi, Gautam; Ma, Zhaowu; Kunnumakkara, Ajaikumar B. (Frontiers in Oncology, 2024)
Ovarian cancer (OVC) is one of the most common causes of cancer deaths in women worldwide.Despite advances in detection and therapy, the prognosis of OVC remains poor due to late diagnosis and the lack of effective therapeutic options at advanced stages. Therefore, a better understanding of the biology underlying OVC is essential for the development of effective strategies for early detection and targeted therapies. Nuclear receptors (NRs) are a superfamily of 48 transcription factors that, upon binding to their specific ligand, play a vital role in regulating various cellular processes such as growth, development, metabolism, and homeostasis. Accumulating number of studies have Accumulating evidence from several studies has shown that their aberrant expression is associated with multiple human diseases. Numerous NRs have shown significant effects in the development of various cancers, including OVC. This review summarizes the recent findings on the role of NRs in OVC, as well as their potential as prognostic and therapeutic markers. Further, the basic structure and signaling mechanism of NRs have also been discussed briefly. Moreover, this review highlights their cellular and molecular mechanisms in chemoresistance and chemosensitization. Further, the clinical trials targeting NRs for the treatment of OVC have also been discussed.